2013
DOI: 10.1128/aac.00486-13
|View full text |Cite
|
Sign up to set email alerts
|

Induction of P-Glycoprotein by Antiretroviral Drugs in Human Brain Microvessel Endothelial Cells

Abstract: The membrane-associated drug transporter P-glycoprotein (P-gp) plays an essential role in drug efflux from the brain. Induction of this protein at the blood-brain barrier (BBB) could further affect the ability of a drug to enter the brain. At present, P-gp induction mediated by antiretroviral drugs at the BBB has not been fully investigated. Since P-gp expression is regulated by ligand-activated nuclear receptors, i.e., human pregnane X receptor (hPXR) and human constitutive androstane receptor (hCAR), these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 48 publications
4
28
0
1
Order By: Relevance
“…A ranking system for the effectiveness with which drugs penetrate into the CNS has demonstrated that patients generally exhibited a lower viral load in the cerebrospinal fluid while receiving antiretrovirals with greater brain-penetrating ability [8] and that this is translated into better neurocognitive outcomes [11]. These findings support the concept that the use of antiretroviral regimens with an improved ability to enter the brain could reduce viral loads Tetronic ® 904-containing polymeric micelles overcome the overexpression of ABCG2 in the blood-brain barrier of rats and boost the penetration of the antiretroviral efavirenz into the CNS in the brain and ultimately prevent HIV-associated neurological complications [12]. However, the presence of an intact blood-brain barrier (BBB) has long been known to restrict the penetration of antiretrovirals into the brain [13].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…A ranking system for the effectiveness with which drugs penetrate into the CNS has demonstrated that patients generally exhibited a lower viral load in the cerebrospinal fluid while receiving antiretrovirals with greater brain-penetrating ability [8] and that this is translated into better neurocognitive outcomes [11]. These findings support the concept that the use of antiretroviral regimens with an improved ability to enter the brain could reduce viral loads Tetronic ® 904-containing polymeric micelles overcome the overexpression of ABCG2 in the blood-brain barrier of rats and boost the penetration of the antiretroviral efavirenz into the CNS in the brain and ultimately prevent HIV-associated neurological complications [12]. However, the presence of an intact blood-brain barrier (BBB) has long been known to restrict the penetration of antiretrovirals into the brain [13].…”
mentioning
confidence: 60%
“…Previously, we have shown that the intestinal permeability of EFV is precluded by the activity of ABCG2 that pumps the drug in the basolateral-to-apical direction [22]. Furthermore, in vitro studies demonstrated that chronic treatment with EFV, among other antiretrovirals, could indirectly induce the expression of another ubiquitous ABC, namely ABCB1 (P-glycoprotein, P-gp) by activation of ligand-activated nuclear receptors known to regulate the expression of this efflux pump [12].…”
mentioning
confidence: 99%
“…Our group and others have previously demonstrated that long-term ARV treatment can upregulate Pgp expression at the blood-brain barrier by directly interacting with orphan nuclear receptors (e.g., pregnane X receptor and constitutive androstane receptor), transcription factors that when activated can upregulate the expression of metabolic enzymes and drug transporters (28,37,38). In particular, atazanavir, efavirenz, ritonavir, and other PIs were found to activate human pregnane X receptor, while abacavir, efavirenz, and nevirapine were found to activate human constitutive androstane receptor (28). Since all HIV ϩ ART-treated subjects enrolled in this study were receiving one or more of these drugs in combination with other ARVs, we propose that the observed upregulation of Pgp expression could be due to the interactions of these ARVs with nuclear receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue inflammation and cytokine secretion are known to alter functional expression of drug transporters and CYP enzymes in other disease states (e.g., inflammatory bowel syndrome) (21). Furthermore, we and other investigators have previously reported that the functional expression of drug transporters in brain parenchyma, blood-brain and bloodtestis barriers, and sigmoid colon epithelium is altered by the HIV antigens, viral infection-associated inflammation, and ARVs (22)(23)(24)(25)(26)(27)(28). The main objective of this study was to investigate the impact of HIV-1 infection and suppressive ART on the expression of intestinal drug transporters and metabolic enzymes in the intestinal mucosa of HIV-infected subjects.…”
mentioning
confidence: 99%
“…Ez az eredmény összefüggést mutat azzal, hogy a vírus a citokinek kiválasztását fokozza, amely szintén növeli a transzporterfehérje-expressziót az agyi kapilláris endothelsejteken és az astrocytákon [62,71]. Ugyanakkor kimutatták, hogy két HIV-ellenes gyógyszer: az atazanavir és a ritonavir növeli a P-gp-expressziót in vitro sejtvonalon és primer human endothelsejt-kultúrán [72,73].…”
Section: Hiv-encephalitisunclassified